Energy cultures and language border in Switzerland - Mehdi Farsi; Martin Péclat; Michael Puntiroli; Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2025)
Energy cultures, broadly defined as shared beliefs, practices, and material preferences that shape energy-related behaviors, provide a useful framework for investigating consumption differences across population groups. We investigate how households' energy demand behavior differ across the French-German language border in Switzerland. Our empirical strategy focuses on a regression discontinuity design, leveraging the clear separation created by the language border. We distinguish between two types of behavior, one linked to mobility and another to electricity consumption. Our results indicate that electricity consumption is relatively stable across the border. On the other hand, households residing in the French-speaking region show on average a greater usage of own vehicle, measured by annual distance traveled. This difference remain significant across the language border, suggesting that cultural elements could drive meaningful differences in private car travel. While we do not find evidence for energy culture differences in electricity demand, our results point to distinct energy cultures with regards to car usage, therefore in the mobility domain.
Keywords: C24; R23; R41; Q40; 330; Energy culture; Household energy demand; Electricity usage; Mobility; Correlated random effects; Regression discontinuity design